2012
DOI: 10.1002/14651858.cd003401.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal-epidural versus epidural analgesia in labour

Abstract: Analysis 2.5. Comparison 2 Combined spinal-epidural versus low-dose epidural, Outcome 5 Number of women who mobilise....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 73 publications
3
168
0
16
Order By: Relevance
“…It is noteworthy that our study showed no hemodynamic differences between the two groups but faster reduction of NRS values in CSEA group at 15 min when exposed to two equianalgesic regimens; this may suggest an additional advantage for CSEA, as it would provide faster and better analgesia at the first stage of labour with no added hemodynamic repercussions. In line with our results, a recent Cochrane Review that compared CSEA and EA involving 3274 women found no difference in maternal hypotension whereas a more rapid onset of analgesia in the CSEA group [21]. Also, we found no significant differences between the two groups regarding urinary retention and rates of operative or instrumental deliveries.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that our study showed no hemodynamic differences between the two groups but faster reduction of NRS values in CSEA group at 15 min when exposed to two equianalgesic regimens; this may suggest an additional advantage for CSEA, as it would provide faster and better analgesia at the first stage of labour with no added hemodynamic repercussions. In line with our results, a recent Cochrane Review that compared CSEA and EA involving 3274 women found no difference in maternal hypotension whereas a more rapid onset of analgesia in the CSEA group [21]. Also, we found no significant differences between the two groups regarding urinary retention and rates of operative or instrumental deliveries.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4] Nevertheless, labour epidural analgesia may be associated with side effects, including prolonged labour, increased incidence of assisted vaginal delivery (AVD), 4,5 reduced ability to ambulate, 6 pruritus, 7 hypotension, 8 requirement for urinary catheterization, 9 and abnormal fetal heart rate. 10 Limiting the dose of local anesthetic and use of adjuvant drugs, such as opioids and epinephrine, may potentially reduce these side effects.…”
Section: Résumémentioning
confidence: 99%
“…19,20 Geliştirilmiş tekniklerle birlikte birçok araştırmacı, dilüe anestezik solüsyonların epidural yolla uygulanmasının sezaryen oranında artışa yol açmadığını bildirmişlerdir. 21 Sharmo ve ark. 14 randomize çalışmanın meta-analizinde epidural analjezinin artmış sezaryen oranı ile ilişkili olmadığını göstermişlerdir.…”
Section: Discussionunclassified